2013
DOI: 10.1016/j.scitotenv.2013.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of PM2.5, PM10 and PM2.5–10 on daily mortality in the Netherlands

Abstract: PM10 and PM2.5 both were significantly associated with all cause and cause-specific mortality. We were unable to demonstrate significant effects for PM2.5-10, possibly due to the lower temporal variability and the higher exposure misclassification in PM2.5-10 compared to PM10 or PM2.5. The lack of effects of PM2.5-10 in our study should therefore not be interpreted as an indication that PM2.5-10 can be considered harmless.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(127 citation statements)
references
References 24 publications
11
111
1
4
Order By: Relevance
“…Studies of 29 European cities [53] showed an increase in daily mortality with an increase in PM 10 concentrations. The impact of particulate matter on daily mortality has been shown by similar studies [54,55]; other studies demonstrated that short-term impacts of PM 10 on mortality were exceeded even at concentrations complying with the European air ambient monitoring regulation [56].…”
Section: Discussionmentioning
confidence: 83%
“…Studies of 29 European cities [53] showed an increase in daily mortality with an increase in PM 10 concentrations. The impact of particulate matter on daily mortality has been shown by similar studies [54,55]; other studies demonstrated that short-term impacts of PM 10 on mortality were exceeded even at concentrations complying with the European air ambient monitoring regulation [56].…”
Section: Discussionmentioning
confidence: 83%
“…Aerosol is an important component of the atmosphere that affects the environment [1][2][3], weather [4], climate [5] and even human health [6][7][8]. Thus, monitoring aerosol properties via both ground-based observations and satellite observations has become important [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In case of the study in Ostrava it was a three-year period. This meets the general requirements that state one year as the minimum time period for a similar type of study (33). However, a longer period is an advantage and allows more accurate determination of the relationship.…”
Section: Fig 4 Average Daily Numbers Of Hospital Admissions In the mentioning
confidence: 71%
“…At present, the optimal size of the population for a similar type of study is considered one million people and more (33). In the literature, however, we can find a number of studies in the cities which population is smaller.…”
Section: Fig 4 Average Daily Numbers Of Hospital Admissions In the mentioning
confidence: 99%